PENGARUH PEMBERIAN EKSTRAK BAWANG PUTIH (ALIUM SATIVUM) TERHADAP TINGKAT KESEMBUHAN DAN KELULUSHIDUPAN KEPITING BAKAU (SCYLLA SERRATA) YANG DIMUTILASI - H Hono; Yuliana Saloso; Cresca B. Eoh (Jurnal Akuatik, 2018)
Abstract - This research aims to determine the effect of Garlic Extract and its maximum dosage on the healing rate and survival rate of mutilated mangrove crab. The method used in this study is laboratory experimental method using a complete randomized design with three treatments and three replications with extract concentration in treatment A (0.1%), treatment B (1%) and treatment C (10%). This research was conducted at the laboratory of the Faculty of Marine and Fisheries of Nusa Cendana University, Kupang. The results shows that the application of garlic extract (Alium sativum) have an effect on the healing rate and survival rate of mutilated mangrove crab with optimal garlic extract concentration of 10% is capable of killing the bacteria that attacked the mangrove crab (Scylla serrata). It is recommended for further research to use 10% concentration to cure and increase the life rate of the mutilated mangrove crab. Keyword : Mangrove Crab, Mutilation, Garlic Extract.